Excessive Adjectives Using the Multiple Affixations ma-hu in Toba Batak - Ambarita, Esron; Panggabean, Himpun; Pasaribu, Dona Enjel Loina (English Lecturers and Teachers Association (ELTA), 2025)
This study aimed to investigate the multiple affixations ma-hu in Toba Batak. This study desired verbal data on the multiple affixationss as the primary data. Secondary data were also taken based on the writer’s knowledge because the writer is a TB native speaker. This study used a qualitative method. The results show that there are four alternating forms of the multiple affixations ma-hu attached to root adjectives, they are, (1) if the final sound of the root adjectives are [k], [n], or [ŋ], the multiple affixations ma-hu has the alternating form [ma-ku], (2) if the final sound of the root adjectives are [m] or [p], the multiple affixations ma-hu has the alternating form [ma-pu], (3) if the final sound of the root adjectives is [s], the multiple affixations ma-hu has the alternating form [ma-su], and (4) if the final sound of the root adjectives is [t], the multiple affixations ma-hu has the alternating form [ma-tu]. The variant form of the multiple affixations ma-hu is pa-hu. Keywords : excessive adjectives; multiple affixations; grammatical functions